THE EFFECT OF FINANCIAL TECHNOLOGY USE AND FINANCIAL LITERACY TOWARDS FINANCIAL INCLUSION IN MANADO (CASE STUDY: FEB STUDENTS IN SAM RATULANGI UNIVERSITY MANADO) - Wewengkang, Caeli B. P.; Mangantar, Maryam; Wangke, Shinta J. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Financial Technology is an important factors in ease to use financial service. In using financial technology, people can save their time and effort to obtain the required use of financial products. As well as financial literacy, financial literacy helps to improve the quality of financial service and contribute to the economic growth and development of a country. Individual needs and financial product, people must have financial literacy to manage their personal finance well. The aim of this research is to find out the influence of financial technology use and financial literacy to FEB Unsrat studentâ€™ financial inclusion. This is a quantitative research and using Multiple Linear Regression as method to analyze the data. The sample size is 100 respondents of FEB students. This research showed that financial technology use and financial literacy simultaneously influence financial inclusion while partially, financial technology use does not have a significant influence to financial inclusion and financial literacy have a significant influence to financial inclusion.Â Keyword: financial technology use, financial literacy, financial inclusion